Cardiopulmonary exercise testing in the Coronavirus disease — 2019 era: Safety and protocol considerations - Duscha, B. D.; Johnson, J. L.; Bennett, W. C.; Ball, K. N.; Mae Fos, L. B.; Reaves, M. A.; Kraus, W. E. (Current Sports Medicine Reports, 2021)
Cardiopulmonary exercise testing (CPX) is a valuable tool in both clinical practice and research settings. Therefore, it is advantageous for human performance laboratories to continue operating during the coronavirus disease 2019 (COVID-19) pandemic. All institutions should adhere to general COVID-19 guidelines provided by the Centers for Disease Control. Because of the testing environment, CPX laboratories must consider additional precautionary safety measures. This article provides recommendations for modifying the CPX protocol to ensure safety for all stakeholders during the pandemic. These modifications are universal across all populations, types of institutions and testing modalities. Preliminary measures include careful review of federal, local, and institutional mandates. The description outlines how to evaluate a testing environment and alter workflow. Guidelines are provided on what specific personal protective equipment should be acquired; as well as necessary actions before, during, and after the CPX test. These precautions will limit the possibility of both clients and staff from contracting or spreading the disease while maintaining testing volume in the laboratory.